PRIMARY PRODUCTIVITY IN RIVER GODAVARI - Rajyalakshmi, T; Premaswarup, T V (Indian Journal of Fisheries, 2011)
Extensive investigations have been conducted on primary productivity in marine environments and in lakes. But investigations in the flowing fresh waters, such as streams and rivers, are very few. Odum (1956, 1957) calculated the primary productivity of thermal springs using diurnal changes in dissolved-oxygen concentration. Owen (1965) while determining productivity detailed some of ^e factors involved in the dissolved-oxygen distribution of the streams.